Preparation method and application of ternary flame-retardant and heat-conducting integrated auxiliary agent for self-carrying heat-conducting channel
By preparing a ternary flame-retardant and thermally conductive integrated additive with a self-contained thermally conductive channel, the problems of flammability and poor thermal conductivity of polyurethane adhesives were solved, and a polyurethane adhesive with high thermal conductivity and high flame retardancy was achieved, thereby improving the reliability and service life of electronic devices.
Patent Information
- Application Number
- CN202411588424.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing polyurethane adhesives are flammable and have poor thermal conductivity, which cannot effectively dissipate the heat generated by electronic components, resulting in reduced reliability and lifespan of electronic devices.
A three-dimensional heat-conducting and flame-retardant integrated additive with self-contained heat-conducting channels is prepared by compounding spherical alumina, flake boron nitride and needle-shaped microcrystalline cellulose, and performing surface activation and chemical grafting to form a three-dimensional heat-conducting channel. Combined with polyphosphoric acid, melamine and pentaerythritol for flame-retardant modification, a polyurethane adhesive with high thermal conductivity and high flame retardancy is prepared.
It significantly improves the thermal conductivity and flame retardant properties of polyurethane adhesives, achieving a thermal conductivity of 2.28 W/M·K and a flame retardant rating of UL94 V-0, while also improving the mechanical properties and thermal stability of the material.
Smart Images

Figure CN119286428A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a preparation method and application of a ternary flame retardant-heat conducting integrated auxiliary agent for a self-supporting heat conducting channel. Background Art
[0002] Polyurethane (PU) adhesives have excellent adhesive properties and are widely used in aerospace, wood decoration, automotive sealants, synthetic leather, coatings, building materials, electronics and other fields. Although polyurethane adhesives have excellent performance, they are flammable materials. Polyurethane adhesives will catch fire almost instantly when exposed to flames, and will release a large amount of heat, smoke, and toxic gases such as carbon monoxide and hydrogen cyanide when burning. Therefore, the use of flame retardants is crucial to the fire safety of polyurethane adhesives, especially in the field of electronic packaging. Electronic components themselves have heat generation, and the thermal conductivity of polyurethane adhesives is usually only 0.15~0.3W / (m∙K), which has almost no thermal conductivity and cannot effectively conduct the heat generated by electronic components. It will not only reduce the reliability and service life of electronic equipment, but also the accumulation of heat can easily cause the adhesive to catch fire. Therefore, how to prepare a polyurethane adhesive that is flame retardant and can efficiently dissipate heat has become an increasingly urgent issue.
[0003] As a natural material, microcrystalline cellulose is widely available and low in cost. Microcrystalline cellulose has a unique orientation. The cellulose chains in its structure are highly ordered in the crystalline region to form a parallel crystalline structure. It is not easy to deform or damage the structure during heat transfer and can form a stable heat conduction path. The cellulose chains in the crystalline region interact with each other through hydrogen bonds, allowing heat to be transferred more efficiently in these regions. The surface of microcrystalline cellulose usually contains hydroxyl (-OH) functional groups, which can react chemically with other materials (such as polymers or fillers). Through chemical modification, other functional groups can be introduced to regulate the properties of microcrystalline cellulose to meet specific application requirements.
[0004] Boron nitride has the characteristics of high thermal conductivity, low density and high dielectric strength. The addition of boron nitride can significantly reduce the dielectric constant of the composite material, making it have excellent performance in electrical insulation. At the same time, the excellent thermal conductivity and chemical stability of boron nitride can effectively enhance the thermal conductivity of the composite material. Adding an appropriate amount of boron nitride to the composite resin can promote the conduction of heat inside the material.
[0005] Alumina has the characteristics of high hardness, high melting point and high thermal conductivity. Alumina is added as a filler to polymers, coatings, adhesives and sealants to improve the mechanical properties, wear resistance and corrosion resistance of the materials. Alumina fillers can also be used in the packaging and heat dissipation materials of electronic devices, which can improve the heat dissipation effect of electronic devices, protect circuit boards and improve their reliability. The present invention aims to synthesize a polyurethane adhesive with high thermal conductivity and flame retardant properties, which has broad application prospects in various fields, especially in the field of electronic packaging. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a ternary flame retardant-thermal conductive integrated additive for a self-supporting heat conductive channel, and the obtained additive is added to a polyurethane adhesive to make it have the advantages of high thermal conductivity, good thermal stability, high flame retardant efficiency, and anti-dripping.
[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a ternary flame retardant-heat conducting integrated additive with a self-supporting heat conducting channel comprises the following steps: (1) Spherical alumina was dispersed in Tris buffer and ultrasonicated for 30 min to obtain a spherical alumina suspension. Dopamine hydrochloride was added and stirred at room temperature for 6 h. KH550 coupling agent was added dropwise and stirred at 60 °C for 5 h. The mixture was filtered and washed, and then dried at 70-80 °C for 12-24 h to obtain an activated spherical alumina thermal conductor. (2) Dispersing flake boron nitride in a mixed solution of Tris buffer and ethanol and ultrasonicating for 30 min to obtain a flake boron nitride suspension, adding dopamine hydrochloride and stirring at room temperature for 6 h, adding KH550 coupling agent dropwise and continuing to stir at 60 °C for 5 h, filtering, washing, and drying at 70-80 °C for 12-24 h to obtain an activated flake boron nitride thermal conductor; (3) Soaking microcrystalline cellulose in an alkaline solution for 3 h, freezing it at -18 °C for 12 h, and then stirring it at room temperature to obtain a uniform microcrystalline cellulose suspension; (4) adding the spherical alumina thermal conductor and the flake boron nitride thermal conductor obtained in step (1) and step (2) to the microcrystalline cellulose suspension obtained in step (3), magnetically stirring at room temperature for 2 hours, centrifuging, discarding the supernatant, washing the precipitate with an ethanol solution until it is neutral, and adding anhydrous ethanol to obtain a surface-activated ternary thermal conductor suspension; (5) Add pentaerythritol to the phosphorus-containing acid, stir magnetically at 140 °C for 1.5 h, slowly add the suspension of melamine and anhydrous ethanol, lower the temperature to 80 °C and continue stirring for 6 h. After the reaction is completed, dry to obtain a flame retardant additive; (6) The flame retardant additive obtained in step (5) is uniformly dispersed in anhydrous ethanol, and then added to the ternary thermal conductive agent suspension obtained in step (4) and stirred for 2 h. Aluminum hydroxide is then added and the reaction is continued for 1 h. After the reaction is completed, the reactant is dried to obtain a flame retardant-thermal conductive integrated additive.
[0008] Furthermore, the mass ratio of dopamine hydrochloride to flaky boron nitride and spherical alumina is 1:5:5; and the amount of KH550 coupling agent used is 2.5 mL per 1 g of dopamine hydrochloride.
[0009] Furthermore, the mass concentration of the alkali solution in step (3) is 5%, and the amount thereof is 200 mL for every 4 g of microcrystalline cellulose, and the alkali solution is one of sodium hydroxide solution and potassium hydroxide solution.
[0010] Furthermore, in step (4), the mass ratio of the activated spherical alumina thermal conductor to the flaky boron nitride thermal conductor is 1:1-2:1; the total mass ratio of microcrystalline cellulose to the thermal conductor is 15:(1-3); and the concentration of the ethanol solution is 60-95%.
[0011] Furthermore, in step (5) and step (6), the molar ratio of pentaerythritol, phosphorus-containing acid, melamine and aluminum hydroxide is 1:2:2:2, and the phosphorus-containing acid is one or more of polyphosphoric acid, phosphoric acid and phytic acid.
[0012] Furthermore, in step (6), the mass ratio of the flame retardant auxiliary agent to the ternary thermal conductor is (2-5):15.
[0013] The present invention also provides a ternary flame retardant-heat conductive integrated auxiliary agent prepared by the above method.
[0014] An application of the above-mentioned ternary flame retardant-thermal conductive integrated additive in polyurethane adhesive is to add the ternary flame retardant-thermal conductive integrated additive to the polyurethane adhesive in an amount of 50-70% of the mass of the polyurethane adhesive.
[0015] The present invention compounds flaky boron nitride and spherical alumina, uses needle-shaped microcrystalline cellulose as an orientation channel, performs surface activation treatment on boron nitride and alumina, and uses a chemical grafting method to carry them on the needle-shaped microcrystalline cellulose to form a three-dimensional heat-conducting channel with a certain orientation. Utilizing the action principle of flame retardants, polyphosphoric acid is used as an acid source, melamine is used as a gas source, and pentaerythritol is used as a main carbon source, and the activated ternary thermal conductor is flame-retardantly modified by combining grafting and coating methods, and the modified ternary flame-retardant-heat-conducting integrated auxiliary agent is added to the polyurethane adhesive by a simple physical blending method to prepare a ternary high-efficiency flame-retardant-heat-conducting polyurethane adhesive with a heat-conducting channel. Microcrystalline cellulose is used as the main "bridge", and through the hydrogen bonding between microcrystalline cellulose and other substances and the esterification reaction of polyphosphoric acid and hydroxyl groups, the thermal conductor and the flame retardant are chemically bonded to form an integrated flame-retardant heat-conducting auxiliary agent, and finally a flame-retardant-heat-conducting integrated polyurethane adhesive is obtained. In addition, the unique structure of microcrystalline cellulose can also improve the poor mechanical properties of composite materials with higher inorganic filling content.
[0016] Beneficial effects of the present invention: (1) The present invention uses spherical aluminum oxide and flake boron nitride as thermal conductive media, selects large-particle flake aluminum nitride as the main medium for heat transfer, and uses small-particle spherical aluminum oxide to supplement the gaps between flake boron nitrides. The two have different shapes and sizes. The compounding of the two can effectively increase the contact area between the thermal conductors, and the introduction of needle-shaped cellulose can provide an oriented channel network, so that the thermal conductive inorganic matter is distributed in an orderly manner, improve the utilization rate of the thermal conductive additive, and promote the transfer of heat in the polyurethane adhesive. Therefore, the synergistic effect of the ternary thermal conductive additive can greatly improve the thermal conductivity of the material. When the thermal conductive additive filling amount is 55%, the thermal conductivity of the polyurethane adhesive can reach 2.28W / M∙K.
[0017] (2) The additive synthesized by the present invention combines flame retardancy and thermal conductivity, has good compatibility with most resin matrices, and can be used as a modification additive for a variety of resin matrices, providing a new method for the multifunctional modification of resin materials. The introduction of microcrystalline cellulose promotes the combination of thermal conductive additives and flame retardant additives to a certain extent, forming a flame retardant-thermal conductive integrated additive, which simplifies the processing technology of the material. In addition, cellulose can also be used as a carbon source for intumescent flame retardants to improve the carbonization rate and flame retardant properties of the material. The flame retardant grade of the modified polyurethane adhesive can reach UL94 V-0. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a synthesis process diagram of the ternary flame retardant-heat conductive integrated auxiliary agent of the present invention.
[0019] Figure 2This is the infrared spectrum of the ternary flame retardant and thermal conductive integrated additive prepared in Example 1.
[0020] Figure 3 This is a scanning electron microscope image of the ternary flame retardant and thermal conductive integrated additive prepared in Example 1.
[0021] Figure 4 This is the energy dispersive X-ray spectrum of the ternary flame retardant and thermal conductive integrated additive prepared in Example 1.
[0022] Figure 5 This is a scanning electron microscope image of the carbon layer of the sample prepared in Application Example 1 after combustion.
[0023] Figure 6 This is a scanning electron microscope image of the carbon layer of the sample prepared in Application Example 2 after combustion.
[0024] Figure 7 This is a scanning electron microscope image of the carbon layer of the sample prepared in Comparative Example 1 after combustion.
[0025] Figure 8 This is a scanning electron microscope image of the carbon layer of the sample prepared in Comparative Example 2 after combustion.
[0026] Fig. 9 This is a scanning electron microscope image of the carbon layer of the sample prepared in Comparative Example 3 after combustion. DETAILED DESCRIPTION
[0027] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0028] Example 1 Pour 200 mL of deionized water into a beaker, slowly add 1.2 g of tris(hydroxymethyl)aminomethane, use hydrochloric acid solution to titrate the system to pH=8.5, and prepare Tris buffer with pH=8.5. Then, slowly add 10 g of spherical alumina with a particle size of about 5~6 µm into the Tris buffer, and ultrasonically disperse for 30 min to obtain a preliminary dispersed and activated alumina suspension; weigh 2 g of dopamine hydrochloride, slowly pour it into the above suspension, add 5 mL of KH550 coupling agent after magnetic stirring at 300 rpm at room temperature for 6 h, and continue stirring at 60 °C for 5 h; finally, filter the mixture, wash it with deionized water, and dry it at 70 °C for 12 h to obtain an activated spherical alumina thermal conductive additive.
[0029] In another beaker, pour 600 mL of deionized water, slowly add 1.2 g of tris(hydroxymethyl)aminomethane to prepare a Tris buffer solution with a pH of 8.5, then add 200 mL of anhydrous ethanol to mix, slowly add 8 g of flake boron nitride with a particle size of about 25 µm to the above solution, and ultrasonically disperse for 30 min to obtain a flake boron nitride suspension after preliminary dispersion and activation; weigh 1.6 g of dopamine hydrochloride, slowly pour it into the above suspension, add 4 mL of KH550 coupling agent after magnetic stirring at 300 rpm at room temperature for 6 h, and continue stirring at 60 °C for 5 h; finally, filter the mixture, wash it with deionized water and anhydrous ethanol respectively, and dry it at 70 °C for 12 h to obtain an activated flake boron nitride thermal conductive additive.
[0030] Weigh 10 g of sodium hydroxide and pour it into 190 mL of deionized water to prepare a sodium hydroxide solution with a mass concentration of 5%, weigh 4 g of microcrystalline cellulose solid powder and add it to the sodium hydroxide solution, and let it stand at room temperature for 3 hours to form a stable suspension; move the suspension to -18 °C and keep it for 12 hours to form a solid frozen material; move it to room temperature and thaw it by mechanical stirring to form a uniform microcrystalline cellulose suspension.
[0031] Weigh 30 g of activated spherical alumina thermal conductive agent and activated flake boron nitride thermal conductive agent, slowly pour them into the microcrystalline cellulose suspension, stir them magnetically at 500 rpm for 2 h at room temperature, centrifuge them at 9000 rpm for 10 min, discard the supernatant, collect the precipitate, wash it with 60%, 70%, 80%, 90%, and 95% ethanol solutions in sequence until it is neutral, weigh 600 mL of anhydrous ethanol, pour it into the reaction system to obtain a surface-activated ternary thermal conductive agent suspension.
[0032] 14.3 g of pentaerythritol was added to 54.2 g of polyphosphoric acid, and the mixture was stirred magnetically at 400 rpm for 1.5 h at 140 °C. 15 g of melamine was weighed and poured into 600 mL of anhydrous ethanol to form a melamine-ethanol suspension, which was slowly added to the above pentaerythritol-polyphosphoric acid product, and the temperature was adjusted to 80 °C. The mixture was stirred magnetically at 500 rpm for 6 h, and the product was moved to a 140 °C oven and dried for 24 h to obtain a flame retardant additive.
[0033] Weigh 8 g of flame retardant additive into 200 mL of anhydrous ethanol, disperse evenly under 500 rpm magnetic stirring at 80 °C to obtain a suspension, slowly add the suspension into the surface activated ternary thermal conductor suspension, magnetically stir for 2 h, add 2.35 g of aluminum hydroxide and continue magnetic stirring for 1 h. Move the product to an 80 °C oven and dry for 12 h to obtain a flame retardant-thermal conductive integrated additive.
[0034] 18.4 g of poly(1,4-butylene adipate) was weighed and placed in a three-necked flask and dehydrated at 80 °C for 3 h. 0.03 g of H8O2 defoamer, 0.015 g of dibutyltin dilaurate and 3.1 g of 1,4-butylene glycol were added dropwise to poly(1,4-butylene adipate), and after magnetic stirring at 500 rpm for 30 s at 80 °C, 42 g of flame retardant-thermal conductive integrated additive was slowly added and stirred for 30 s. After the system was stirred evenly, 1.6 g of hexamethylene diisocyanate was slowly added and stirred for 1 min to obtain a ternary flame retardant-thermal conductive polyurethane adhesive with a self-supporting thermal conductive channel.
[0035] Figure 2 This is the infrared spectrum of the ternary flame retardant and thermal conductive integrated additive prepared in Example 1. It can be seen from the figure that the stretching vibration of the hydroxyl group in the structure of dopamine hydrochloride causes the activated boron nitride and aluminum oxide to emit an infrared spectrum at 3380 cm -1 、1630 cm -1 There are obvious broad absorption peaks at all locations, indicating that boron nitride and aluminum oxide are successfully activated by dopamine hydrochloride. At the same time, the stretching vibration of the hydroxyl group in the microcrystalline cellulose structure is also at 3380 cm -1 、1630 cm -1 There is a broad absorption peak near 3380 cm -1 、1630 cm -1 The broad absorption peak caused by the hydroxyl stretching vibration in the activated boron nitride and alumina structures and microcrystalline cellulose structures is weakened, indicating that the original hydroxyl functional groups are consumed as the chemical reaction proceeds, and the intensity of the broad absorption peak is weakened. In addition, the CH bending vibration and COC (ether bond) stretching vibration peaks (1390 cm -1 and 1070 cm -1 ) also appears in the infrared spectrum of the ternary flame retardant and thermal conductive integrated additive, which shows that after boron nitride and aluminum oxide are activated by dopamine hydrochloride, they can smoothly undergo chemical grafting reaction with microcrystalline cellulose. Figure 3 , 4 They are respectively the scanning electron microscope image and the energy dispersive X-ray spectrum image of the ternary flame retardant and thermal conductive integrated additive prepared in Example 1. Figure 3 It can be seen that the ternary flame retardant and thermal conductive integrated additive is distributed in a network. This is because the activated boron nitride and aluminum oxide form hydrogen bonds with microcrystalline cellulose, which allows the thermal conductive inorganic substances to be distributed along the whisker structure of microcrystalline cellulose in a certain orientation, thus constructing a three-dimensional network thermal conductive channel. And through the energy dispersive X-ray spectrum of the ternary flame retardant and thermal conductive integrated additive Figure 4 It can be seen that the main flame retardant elements C, N, and P are also distributed along the veins of the network structure, which indicates that the flame retardant additives are successfully chemically combined with the activated boron nitride and aluminum oxide at the molecular level.
[0036] Example 2 Pour 200 mL of deionized water into a beaker, slowly add 1.2 g of tris(hydroxymethyl)aminomethane, use hydrochloric acid solution to titrate the system to pH=8.5, and prepare Tris buffer with pH=8.5. Then, slowly add 10 g of spherical alumina with a particle size of about 5~6 µm into the Tris buffer, and ultrasonically disperse for 30 min to obtain a preliminary dispersed and activated alumina suspension; weigh 2 g of dopamine hydrochloride and slowly pour it into the above suspension, add 5 mL of KH550 coupling agent after magnetic stirring at 300 rpm at room temperature for 6 h, and continue stirring at 60 °C for 5 h; finally, filter the mixture, wash it with deionized water, and dry it at 70 °C for 12 h to obtain an activated spherical alumina thermal conductive additive.
[0037] In another beaker, pour 600 mL of deionized water, slowly add 1.2 g of tris(hydroxymethyl)aminomethane to prepare a Tris buffer solution with a pH of 8.5, then add 200 mL of anhydrous ethanol to mix, slowly add 8 g of flake boron nitride with a particle size of about 25 µm to the above solution, and ultrasonically disperse for 30 min to obtain a flake boron nitride suspension after preliminary dispersion and activation; weigh 1.6 g of dopamine hydrochloride, slowly pour it into the above suspension, add 4 mL of KH550 coupling agent after magnetic stirring at 300 rpm at room temperature for 6 h, and continue stirring at 60 °C for 5 h; finally, filter the mixture, wash it with deionized water and anhydrous ethanol respectively, and dry it at 70 °C for 12 h to obtain an activated flake boron nitride thermal conductive additive.
[0038] Weigh 10 g of sodium hydroxide and pour it into 190 mL of deionized water to prepare a sodium hydroxide solution with a mass concentration of 5%, weigh 4 g of microcrystalline cellulose solid powder and add it to the sodium hydroxide solution, and let it stand for 3 hours at room temperature to form a stable suspension; move the suspension to -18 °C and keep it for 12 hours to form a solid frozen product; move it to room temperature and thaw it by mechanical stirring to form a uniform microcrystalline cellulose suspension.
[0039] Weigh 40 g of activated spherical alumina thermal conductive agent and 20 g of activated flake boron nitride thermal conductive agent, slowly pour them into the microcrystalline cellulose suspension, stir magnetically at 500 rpm for 2 h at room temperature, centrifuge at 9000 rpm for 10 min, discard the supernatant, collect the precipitate, wash it with 60%, 70%, 80%, 90%, and 95% ethanol solutions in sequence until the system is neutral, weigh 600 mL of anhydrous ethanol, pour it into the reaction system to obtain a surface-activated ternary thermal conductive agent suspension.
[0040] 14.3 g of pentaerythritol was added to 54.2 g of polyphosphoric acid, and the mixture was stirred magnetically at 400 rpm for 1.5 h at 140 °C. 15 g of melamine was weighed and poured into 600 mL of anhydrous ethanol to form a melamine-ethanol suspension, which was slowly added to the above pentaerythritol-polyphosphoric acid product, and the temperature was adjusted to 80 °C. The mixture was stirred magnetically at 500 rpm for 6 h, and the product was moved to a 140 °C oven and dried for 24 h to obtain a flame retardant additive.
[0041] Weigh 8 g of flame retardant additive into 200 mL of anhydrous ethanol, disperse evenly at 80 °C with 500 rpm magnetic stirring, slowly add the uniform suspension into the surface activated ternary thermal conductor suspension and magnetically stir for 2 h, then add 2.35 g of aluminum hydroxide and continue magnetic stirring for 1 h. Move the product to an 80 °C oven and dry it for 12 h to obtain a flame retardant-thermal conductive integrated additive.
[0042] 18.4 g of poly(1,4-butylene adipate) was weighed and placed in a three-necked flask and dehydrated at 80 °C for 3 h. 0.03 g of H8O2 defoamer, 0.015 g of dibutyltin dilaurate and 3.1 g of 1,4-butylene glycol were added dropwise to poly(1,4-butylene adipate), and after magnetic stirring at 500 rpm for 30 s at 80 °C, 42 g of flame retardant-thermal conductive integrated additive was slowly added and stirred for 30 s. After the system was stirred evenly, 1.6 g of hexamethylene diisocyanate was slowly added and stirred for 1 min to obtain a ternary flame retardant-thermal conductive polyurethane adhesive with a self-supporting thermal conductive channel.
[0043] Comparative Example 1 18.4 g of poly(1,4-butylene adipate) was weighed and placed in a three-necked flask and dehydrated at 80 °C for 3 h. 0.03 g of H8O2 defoamer, 0.015 g of dibutyltin dilaurate and 3.1 g of 1,4-butylene glycol were added dropwise to poly(1,4-butylene adipate), and after magnetic stirring at 500 rpm for 30 s at 80 °C, 1.6 g of hexamethylene diisocyanate was slowly added dropwise and stirred for 1 min to obtain a polyurethane adhesive.
[0044] Comparative Example 2 Weigh 8 g of flame retardant additive into 200 mL of anhydrous ethanol, disperse evenly under 500 rpm magnetic stirring at 80 °C, add 15 g each of activated spherical alumina thermal conductive additive and flake boron nitride thermal conductive additive, stir for 2 h, add 1.18 g of aluminum hydroxide and continue magnetic stirring for 1 h. Move the product to an 80 °C oven and dry for 12 h to obtain a binary flame retardant thermal conductive additive.
[0045] 18.4 g of poly(1,4-butylene adipate) was weighed and placed in a three-necked flask and dehydrated at 80 °C for 3 h. 0.03 g of H8O2 defoamer, 0.015 g of dibutyltin dilaurate and 3.1 g of 1,4-butylene glycol were added dropwise to poly(1,4-butylene adipate), and after magnetic stirring at 500 rpm for 30 s at 80 °C, 42 g of binary flame retardant thermal conductive additive was slowly added and stirred for 30 s. After the system was stirred evenly, 1.6 g of hexamethylene diisocyanate was slowly added and stirred for 1 min to obtain a binary thermal conductive polyurethane adhesive.
[0046] Comparative Example 3 18.4 g of poly(1,4-butylene adipate) was weighed and placed in a three-necked flask and dehydrated at 80 °C for 3 h. 0.03 g of H8O2 defoamer, 0.015 g of dibutyltin dilaurate and 3.1 g of 1,4-butylene glycol were added dropwise to poly(1,4-butylene adipate), and after magnetic stirring at 500 rpm for 30 s at 80 °C, 8 g of flame retardant additive, 10 g of spherical alumina, 20 g of flake boron nitride and 4 g of microcrystalline cellulose were slowly added and stirred for 30 s. After the system was stirred evenly, 1.6 g of hexamethylene diisocyanate was slowly added dropwise and stirred for 1 min to obtain a thermally conductive polyurethane adhesive.
[0047] Application Example 1 The ternary flame retardant-thermal conductive polyurethane adhesive of the self-supporting heat-conducting channel obtained in Example 1 was hot-pressed by a flat vulcanizer to prepare flame retardant performance test specimens (length × width × thickness = 130 mm × 10 mm × 3.2 mm), mechanical properties standard test specimens and thermal conductivity test specimens (length × width × thickness = 40 mm × 40 mm × 5 mm) for testing.
[0048] The results show that the vertical burning test grade of the sample can reach UL94 V-0, the LOI value is 35.3%, the elongation at break is 7.9%, the tensile strength is 45.1 MPa, and the residual carbon rate of the flame retardant sample after full carbonization at 600 °C in a muffle furnace is 54.1%, and the thermal conductivity is 2.28 W / m∙k.
[0049] Application Example 2 The ternary flame retardant-thermal conductive polyurethane adhesive of the self-supporting heat-conducting channel obtained in Example 2 was hot-pressed by a flat vulcanizer to prepare flame retardant performance test specimens (length × width × thickness = 130 mm × 10 mm × 3.2 mm), mechanical properties standard test specimens and thermal conductivity test specimens (length × width × thickness = 40 mm × 40 mm × 5 mm) for testing.
[0050] The results show that the vertical burning test grade of the sample can reach UL94 V-0, the LOI value is 28.5%, the elongation at break is 8.4%, the tensile strength is 48.4 MPa, and the residual carbon rate of the flame retardant sample after full carbonization at 600 °C in a muffle furnace is 54.38%, and the thermal conductivity is 1.6 W / m∙k.
[0051] Figure 5 , 6 The scanning electron microscope images of the carbon layer after combustion of the sample strips prepared in Example 1 and Example 2 are shown respectively. It can be seen from the figure that the large amount of residual inorganic matter and the residual carbon form a dense layered structure, and there are no large holes on the surface, indicating that it plays a role in blocking the heat source, and thus has good flame retardant properties.
[0052] Application Comparative Example 1 The polyurethane obtained in Comparative Example 1 was hot-pressed by a flat vulcanizer to prepare flame retardant test strips (length × width × thickness = 130 mm × 10 mm × 3.2 mm), mechanical properties standard test strips and thermal conductivity test blocks (length × width × thickness = 40 mm × 40 mm × 5 mm) for testing.
[0053] The results show that the vertical burning test grade of the sample is UL94 NR, the LOI value is 18.2%, the elongation at break is 461.6%, the tensile strength is 12.35 MPa, the residual carbon rate of the flame retardant sample after full carbonization at 600 °C in a muffle furnace is 0.2%, and the thermal conductivity is 0.23 W / m∙k.
[0054] Figure 7 This is a scanning electron microscope image of the carbon layer after burning the sample prepared in Comparative Example 1. As can be seen from the figure, the carbon layer is rough and has large holes, which cannot effectively block the heat source and does not achieve the ideal flame retardant effect.
[0055] Application Comparative Example 2 The polyurethane obtained in Comparative Example 2 was hot-pressed by a flat vulcanizer to prepare flame retardant test strips (length × width × thickness = 130 mm × 10 mm × 3.2 mm), mechanical properties standard test strips and thermal conductivity test blocks (length × width × thickness = 40 mm × 40 mm × 5 mm) for testing.
[0056] The results show that the vertical burning test grade of the sample is only UL94 V-1, the LOI value is 26.8%, the elongation at break is 8.0%, the tensile strength is 10.6 MPa, the mechanical properties are reduced, and the residual carbon rate of the flame retardant sample after full carbonization at 600 °C in a muffle furnace is 52.1%, and the thermal conductivity is 1.53 W / m∙k.
[0057] Figure 8 The scanning electron microscope image of the carbon layer after combustion of the sample prepared in comparative application example 2. It can be seen from the figure that only a partial layered structure is formed, and the carbon layer has many holes and is relatively uneven as a whole, which cannot effectively block the heat source and does not achieve the ideal flame retardant effect.
[0058] Application Comparative Example 3 The thermally conductive polyurethane adhesive obtained in Comparative Example 3 was hot-pressed by a flat vulcanizer to prepare flame retardant test strips (length × width × thickness = 130 mm × 10 mm × 3.2 mm), mechanical properties standard test strips and thermal conductivity test blocks (length × width × thickness = 40 mm × 40 mm × 5 mm) for testing.
[0059] The results show that the vertical burning test grade of the sample is only UL94 V-1, the LOI value is 24.0%, the elongation at break is 1.1%, the tensile strength is 22.5 MPa, the mechanical properties are reduced, and the residual carbon rate of the flame retardant sample after full carbonization at 600 °C in a muffle furnace is 53.34%, and the thermal conductivity is 2 W / m∙k.
[0060] Fig. 9The scanning electron microscope image of the carbon layer after burning the sample prepared in Example 3 is used for comparison. The inorganic matter and the residual carbon are arranged sparsely, and there are large gaps between the inorganic matter and the residual carbon, which cannot effectively block the heat source and fail to achieve the ideal flame retardant effect.
[0061] By comparing Application Examples 1-2 and Comparative Examples 1-3, it can be seen that: (1) The present invention uses three different shapes of thermal conductors: spherical aluminum oxide, flake boron nitride, and needle-shaped microcrystalline cellulose. The needle-shaped microcrystalline cellulose is used as a channel, and the spherical aluminum oxide and flake boron nitride are used as the main thermal conductive medium to construct a three-dimensional thermal conductive channel inside the polyurethane adhesive. In terms of chemical modification, the needle-shaped microcrystalline cellulose is used as the main chemical grafting "bridge" to enable the thermal conductor and the flame retardant to be effectively combined into one, thereby generating a flame retardant-thermal conductive integrated additive.
[0062] (2) The different ratios of the two activated thermal conductive media will greatly affect the thermal conductivity of the final polyurethane adhesive. A high proportion of boron nitride can significantly improve the thermal conductivity of the polyurethane adhesive, but at the same time, since the processability of boron nitride itself is lower than that of alumina, this will lead to a certain degree of deterioration of the mechanical properties of the polyurethane adhesive when the proportion of boron nitride added increases.
[0063] (3) The thermal conductivity of binary polyurethane adhesive is low, the thermal conductivity coefficient is not high, the thermal conductive medium cannot achieve efficient contact, and there is no certain thermal conductivity orientation inside the material. Therefore, a higher amount of thermal conductive agent filling is usually required to make the thermal conductivity coefficient of the product meet the qualified standard. Due to the large amount of additive filling, the mechanical properties of the composite material are greatly reduced. At the same time, the flame retardant effect of binary polyurethane adhesive is poor, the overall carbon content of the material is insufficient, and it cannot achieve effective combustion inhibition.
[0064] (4) Although the thermal conductivity of the material can be improved to a certain extent by directly blending the ternary thermal conductive additive with the polyurethane adhesive, the contact area of the medium is small and the thermal conductivity coefficient is not high because the thermal conductive medium is not modified and there is no targeting between the media. At the same time, the unmodified additive has poor compatibility with polyurethane, and the mechanical properties of the final composite material drop sharply.
[0065] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a ternary flame retardant and thermal conductive integrated additive for a self-supporting thermal conductive channel, characterized in that: The following steps are involved: (1) Spherical alumina was dispersed in Tris buffer and ultrasonicated for 30 min to obtain a spherical alumina suspension. Dopamine hydrochloride was added and stirred at room temperature for 6 h. KH550 coupling agent was added dropwise and stirred at 60 °C for 5 h. The mixture was filtered and washed, and then dried at 70-80 °C for 12-24 h to obtain an activated spherical alumina thermal conductor. (2) Dispersing flake boron nitride in a mixed solution of Tris buffer and ethanol and ultrasonicating for 30 min to obtain a flake boron nitride suspension, adding dopamine hydrochloride and stirring at room temperature for 6 h, adding KH550 coupling agent dropwise and continuing to stir at 60 °C for 5 h, filtering, washing, and drying at 70-80 °C for 12-24 h to obtain an activated flake boron nitride thermal conductor; (3) Soaking microcrystalline cellulose in an alkaline solution for 3 h, freezing it at -18 °C for 12 h, and then stirring it at room temperature to obtain a uniform microcrystalline cellulose suspension; (4) adding the spherical alumina thermal conductor and the flake boron nitride thermal conductor obtained in step (1) and step (2) to the microcrystalline cellulose suspension obtained in step (3), magnetically stirring at room temperature for 2 hours, centrifuging, discarding the supernatant, washing the precipitate with an ethanol solution until it is neutral, and adding anhydrous ethanol to obtain a surface-activated ternary thermal conductor suspension; (5) Add pentaerythritol to the phosphorus-containing acid, stir magnetically at 140 °C for 1.5 h, slowly add the suspension of melamine and anhydrous ethanol, lower the temperature to 80 °C and continue stirring for 6 h. After the reaction is completed, dry to obtain a flame retardant additive; (6) The flame retardant additive obtained in step (5) is uniformly dispersed in anhydrous ethanol, and then added to the ternary thermal conductive agent suspension obtained in step (4) and stirred for 2 h. Aluminum hydroxide is then added and the reaction is continued for 1 h. After the reaction is completed, the reactant is dried to obtain a flame retardant-thermal conductive integrated additive.
2. The preparation method according to claim 1, characterized in that: The mass ratio of dopamine hydrochloride to flake boron nitride and spherical alumina is 1:5:5; the amount of KH550 coupling agent used is 2.5 mL per 1 g of dopamine hydrochloride.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the alkali solution in step (3) is 5%, and the amount used is 200 mL for every 4 g of microcrystalline cellulose. The alkali solution is one of sodium hydroxide and potassium hydroxide solution.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the activated spherical alumina thermal conductor and the flaky boron nitride thermal conductor in step (4) is 1:1-2:1; the total mass ratio of microcrystalline cellulose to the thermal conductor is 15:(1-3); and the concentration of the ethanol solution is 60-95%.
5. The preparation method according to claim 1, characterized in that: The molar ratio of pentaerythritol, phosphorus-containing acid, melamine and aluminum hydroxide in step (5) and step (6) is 1:2:2:2, and the phosphorus-containing acid is one or more of polyphosphoric acid, phosphoric acid and phytic acid.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the flame retardant additive to the ternary thermal conductor in step (6) is (2-5):
15.
7. The ternary flame retardant-thermal conductive integrated auxiliary agent prepared by the method according to any one of claims 1 to 6.
8. Use of the ternary flame retardant and thermal conductive integrated additive as claimed in claim 7 in polyurethane adhesive, characterized in that: The ternary flame retardant and thermal conductive integrated auxiliary agent is added to the polyurethane adhesive, and the added amount is 50-70% of the mass of the polyurethane adhesive.
Citation Information
Patent Citations
Insulating high-thermal-conductivity gel filled with composite thermal conductive filler based on chemical bond assembly
CN113308121A
Thermally expandable refractory material composition, thermally expandable refractory material, and method for producing thermally expandable refractory material
CN116438264A
Heat-conducting flame-retardant insulating adhesive, insulating protective film and preparation method
CN117487487A